ChemInform Abstract: Independent Ordering of Two Interpenetrating Magnetic Sublattices in the Double Perovskite Sr2CoOsO6. Issue 17 (28th April 2014) - Morrow, Ryan; Mishra, Rohan; Restrepo, Oscar D.; Ball, Molly R.; Windl, Wolfgang; Wurmehl, Sabine; Stockert, Ulrike; Buechner, Bernd; Woodward, Patrick M.
Abstract The title compound is prepared by solid state reaction of stoichiometric mixtures of SrO2, Co3O4, and Os metal using PbO2 as an in situ source of oxygen gas (1000 °C, 48 h).